Relative Efficiency of Different Am Fungi on Biomass Production and Nutrient Uptake in Tamarix aphylla - Panwar, Jitendra; Vyas, Anil (Indian Forester, 2002)
Eight arbuscular mycorrhizal species namely Acau[ospora mellea, Gigaspora gigantea, G. margarita, Glomus deserticola, G. fasciculatum, Sclerocystis rubifromis, Scutellospora calospora and S. nigra, collected from rhizosphere soils of T. aphylla from arid and semi-arid regions of India were cultured on Cenchrus ciliaris. Pot cultures of these eight species were used to inoculate T. aphylla in order to assess effect of these AM fungi on biomass production and nutrient uptake. Out of these AM species, Scutellospora calospora was found to be the most significant in increasing plant biomass and nutrient uptake.